Implementation of Differentiated Learning Content Based on Learning Readiness on the Material of the Sine Rule in Grade XI of Senior High School - Siringoringo, Putri Violenta; Napitupulu, Bettisari; Panjaitan, Agnes Teresa; Lumbantobing, Happy; Hadiyanti, Yosefin Rianita (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This research is a descriptive qualitative research that aims to describe the implementation of content differentiated learning based on students' learning readiness on Sine Rule material in class XI-7 SMA Negeri 1 Jayapura. The subjects of this study amounted to 34 students who were selected using purposive sampling technique. The instruments used include teaching modules, diagnostic assessments, teacher observation sheets and individual tests. Before learning, a diagnostic assessment was conducted to categorize students into three categories of learning readiness, namely low, medium and high. The assessment results showed that the learners were divided into 7 groups: 3 low groups, 2 medium groups, and 2 high groups. The implementation of content differentiated learning based on the assessment results went very well. This is shown by the results of teacher observation by the math teacher observer of 88.175% and by the co-researcher of 90.625%, both of which are included in the excellent category. The individual test results showed that 30 out of 34 learners reached the Minimum Completion Criteria (KKM), while the 4 learners who were not complete came from groups with low learning readiness.